Regional determinants of firm entry in a developing country - Calá, Carla Daniela (2012)
Regional policies aiming to attract new firms are largely based on evidence that originates from Europe, the USA and Japan. This may raise doubts about the usefulness of such policies when applied to developing economies. This paper addresses this issue by providing estimates of the determinants of firm entry in the Argentinean provinces. We find that most of the determinants used in previous studies analysing developed countries are still relevant. However, there is a need for additional explanatory variables that reflect the specificities of developing economies.